Analysis of the Influence of Public Participation Against the Success of Community-Based Sanitation Program (SANIMAS) in Paciran Village, Paciran District, Lamongan Regency - Dhiyas Yudi Prakoswo; Bambang Syairudin (Institut Teknologi Sepuluh Nopember, 2019)
Sanimas program in East Java province has been implemented from 2003 and based on the results of monitoring conducted on the sustainability of the Sanimas program as much as 30% work only partially and 8% does not work. Failure in achieving the result of the development program did not reach the target due to lack of community participation In 2017, the Directorate General of Human Settlements, the Ministry of Public Works and Housing has a project in the form of community-based Sanitation development (SANIMAS) located in Paciran village, Paciran district, Lamongan regency, which is a communal waste water treatment with an initial number of users 55 patriarch. The SANIMAS Program in Paciran Village can be assessed successfully because it still works well and is able to increase its service number significantly. There were 93 new participant in the period of 1 year so that the total users reached 148 patriarch. This research is to examine dominant factors in the community participation that affects to the success of the Sanimas program in Paciran village. Start by spreading the questionnaires to the resident of Paciran village who participated in the SANIMAS program. Once collected data is further analyzed with a quantitative descriptive approach. SPSS analysis tools are used to determine the factors by analyzing internal factors including age variables, gender, occupation, amount of income, number of families, education level, and knowledge of SANIMAS. While the external factors include the role of local governments, the role of village government, the role of community leaders, the role of facilitators/ consultants and the role of regional regulations/ LAWS. From the results of analysis obtained the dominant internal factors affecting the form and level of community participation is age, knowledge SANIMAS, the amount of income, type of work, level of education and the number of families. While the dominant external factors affecting the form and the level of community participation is the local regulation/ law and local government. The proposed policy to increase the success achievement of the SANIMAS program in Paciran village is that KPP will routinely held a meetings with RT and RW and to find solutions related to emerging issues and socialization to citizens will be conducted with the approach of citizen activities such as community gathering, moslem recitation etc